Deradicalization in Textbooks of Islamic Religious Education Material with Radicalism in Schools - A. Jauhar Fuad; Muhammad ‘Arifuddin (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2021)
This article is limited to a literature study dealing with radicalization in educational institutions. More specifically, the authors want to add as much information as possible, so that this paper strengthens the study of literature and data that can strengthen further research. The preliminary results are as follows: radicalism enters through textbooks, by changing the religious understanding of teachers and students, the books used are official books published by the government and private institutions through worksheets. Based on the above problems, the author has indeed tried to look back at some of the teaching materials for Islamic religious education which are mixed with radical ideas as revised by the government and by the community to improve textbooks so that radical understanding can be lost. So it is necessary to reorientate the handling of radicalization which has been done and understood by great people. Efforts to stem radicalism, which have so far been more focused on terrorists or warfighters, have not been carried out much as an understood precaution and radical action.